Efficient charge generation by relaxed charge-transfer states at organic interfaces - Vandewal, K; Albrecht, S; Hoke, E; Graham, K; Graham, K; Widmer, J; Douglas, J; Schubert, M; Mateker, W; Bloking, J; Burkhard, G; Sellinger, A; et al. (Nature Publishing Group, 2014)
Interfaces between organic electron-donating (D) and electron-accepting (A) materials have the ability to generate charge carriers on illumination. Efficient organic solar cells require a high yield for this process, combined with a minimum of energy losses. Here, we investigate the role of the lowest energy emissive interfacial charge-transfer state (CT1) in the charge generation process. We measure the quantum yield and the electric field dependence of charge generation on excitation of the charge-transfer (CT) state manifold via weakly allowed, low-energy optical transitions. For a wide range of photovoltaic devices based on polymer:fullerene, small-molecule:C60 and polymer:polymer blends, our study reveals that the internal quantum efficiency (IQE) is essentially independent of whether or not D, A or CT states with an energy higher than that of CT1 are excited. The best materials systems show an IQE higher than 90% without the need for excess electronic or vibrational energy. © 2014 Macmillan Publishers Limited.